Using a Biomimicry Approach in the Design of a Kinetic Façade to Regulate the Amount of Daylight Entering a Working Space - Sukhum Sankaewthong; Teerayut Horanont; Kazunori Miyata; Jessada Karnjana; Chawee Busayarat; Haoran Xie (Buildings, 2022)
At present, buildings are increasingly being designed with transparent materials, with glass paneling being especially popular as an installation material due to its architectural allure. However, its major drawback is admitting impractical amounts of sunlight into interior spaces. Office buildings with excessive sunlight in indoor areas lead to worker inefficiency. This article studied kinetic façades as means to provide suitable sunlight for interior spaces, integrated with a triple-identity DNA structure, photosynthetic behavior, and the twist, which was divided into generation and evaluation. The generating phase first used an evolutionary engine to produce potential strip patterns. The kinetic façade was subsequently evaluated using the Climate Studio software to validate daylight admission in an indoor space with Leadership in Energy and Environmental Design (LEED) version 4.1 criteria. To analyze the kinetic façade system, the building envelope was divided into four types: glass panel, static façade, rotating façade (the kinetic façade, version 1); an existing kinetic façade that is commonly seen in the market, and twisting façade (the kinetic façade, version 2); the kinetic façade that uses the process to invent the new identity of the façade. In addition, for both the rotating façade and twisting façade, the degrees of simulation were 20, 50, 80, and 100 degrees, in order to ascertain the potential for both façades to the same degree. Comparing all façades receiving the daylight factor (DF) into the space with more or less sunlight resulted in a decreasing order of potential, as follows: entirely glass façade, twisting façade (the kinetic façade, version 2), rotating façade (the kinetic façade, version 1), and static façade. By receiving the daylight factor (DF), the façade moderately and beneficially filtered appropriate amounts of daylight into the working space. The daylight simulation results indicated that the newly designed kinetic façade (version 2) had more potential than other building envelope types in terms of filtering beneficial daylight in indoor areas. This article also experimented with the kinetic façade prototype in an actual situation to test conditional environmental potential. The twisting façade (the kinetic façade, version 2) was explored in the building envelope with varied adaptability to provide sunlight and for private-to-public, public-to-private, or semi-public working areas.